Second European quality of life survey evaluating the quality of society and public services - Rose, Richard; Newton, Kenneth; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2010)
A person's quality of life is not only shaped by individual choices and behaviour: the surrounding environment and the public services on offer have a big influence on how people perceive the society they live in and on their evaluation of their own quality of life. Institutions influence the quality of society through collective actions that individuals cannot undertake themselves: for example maintaining schools, hospitals and roads. Public policies are also responsible for ensuring that water and air are not polluted, and for reducing tensions between different social groups. If public policies are effective and these services are provided to a high standard, the quality of society will improve, with a positive impact on the overall quality of life of citizens.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Social surveys -- European Union countries; Europe -- Social conditions -- 21th century; Electronic books